2009
DOI: 10.1021/la902129k
|View full text |Cite
|
Sign up to set email alerts
|

Wrinkled, Dual-Scale Structures of Diamond-Like Carbon (DLC) for Superhydrophobicity

Abstract: We present a simple two-step method to fabricate dual-scale superhydrophobic surfaces by using replica molding of poly(dimethylsiloxane) (PDMS) micropillars, followed by deposition of a thin, hard coating layer of a SiO(x)-incorporated diamond-like carbon (DLC). The resulting surface consists of microscale PDMS pillars covered by nanoscale wrinkles that are induced by residual compressive stress of the DLC coating and a difference in elastic moduli between DLC and PDMS without any external stretching or therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
86
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 46 publications
4
86
0
1
Order By: Relevance
“…Furthermore, hydrophobic fi lms have been successfully deposited on patterned substrates to fabricate superhydrophobic surfaces. Rahmawan et al reported a superhydrophobic surface consisting of a SiO x -DLC fi lm and micropillars of poly(dimethylsiloxane) (PDMS) [ 18 ]. The static contact angle of the fi lm on a Si wafer was measured to be 106.4°.…”
Section: Development Of Hydrophobic Surfaces Using Dlcbased Materialsmentioning
confidence: 99%
“…Furthermore, hydrophobic fi lms have been successfully deposited on patterned substrates to fabricate superhydrophobic surfaces. Rahmawan et al reported a superhydrophobic surface consisting of a SiO x -DLC fi lm and micropillars of poly(dimethylsiloxane) (PDMS) [ 18 ]. The static contact angle of the fi lm on a Si wafer was measured to be 106.4°.…”
Section: Development Of Hydrophobic Surfaces Using Dlcbased Materialsmentioning
confidence: 99%
“…Researches can be roughly divided into two groups concerning to wrinkles application. First is to be the functional patterned surface, such as superhydrophobic coating 5) , high light-harvesting ef ciency device 6) , template for aligning colloidal particles 7) and living cells 8) , tunable optical grating 9) and so on. Second is as a strategy for measuring thickness, elastic moduli, Poisson s ratio, and residual stress 10,11) due to its sensitivity to the mechanical and thermal properties of the system.…”
Section: Introductionmentioning
confidence: 99%
“…15) In addition, it is a well-established system to get the averaged wavelength of wrinkles since it can minimize measurement error and quickly provide the indispensable information in spite of the diversity and complexity of samples for both off-line and in-situ observation. 5,[16][17][18][19] However, wrinkle surface morphology could also be predicted other than the wavelength by understanding the derivation mechanism from wrinkles to diffraction patterns, which is lacking at present.…”
Section: Introductionmentioning
confidence: 99%
“…Lotus leaves exhibit low resistance to water condensation owing to the low aspect ratio (defined as the ratio of the height to the width of the structures, ca. 2 or 3) of the nanopillar structure geometries for nanopillar structures (Cha et al, 2010;Cheng et al, 2005;Rahmawan et al, 2010). The water condensation behavior of particular functional organic surfaces has been measured using environmental scanning electron microscopy (ESEM).…”
Section: Introductionmentioning
confidence: 99%